Platelet–lymphocyte ratio predicts survival in patients with hepatocellular carcinoma who receive lenvatinib: an inverse probability weighting analysis. Issue 2 (February 2021) - Tada, Toshifumi; Kumada, Takashi; Hiraoka, Atsushi; Michitaka, Kojiro; Atsukawa, Masanori; Hirooka, Masashi; Tsuji, Kunihiko; Ishikawa, Toru; Takaguchi, Koichi; Kariyama, Kazuya; Itobayashi, Ei; Tajiri, Kazuto; et al.
Abstract : Objective: Lenvatinib, a newly developed molecularly targeted agent, has become available as a first-line therapy in patients with unresectable hepatocellular carcinoma (HCC). The platelet-to-lymphocyte ratio (PLR) has been associated with poor outcome in various malignancies, including HCC. In this study, we investigated the ability of PLR to predict outcomes in patients with unresectable HCC who received lenvatinib. Methods: Multivariate survival analysis was performed in 283 patients with unresectable HCC who received lenvatinib. In addition, the utility of PLR for predicting survival was clarified using an inverse probability weighting (IPW) analysis. Results: Cumulative overall survival at 100, 200, 300, 400, and 500 days was 95.2, 83.8, 68.3, 60.3, and 49.9%, respectively. Multivariate analysis with Cox proportional hazards modeling showed that PLR (≥150) [hazard ratio, 1.588; 95% confidence interval (CI), 1.039–2.428; P  = 0.033], α-fetoprotein level, and Barcelona clinic liver cancer stage were independently associated with overall survival. Cumulative overall survival differed significantly between patients with low versus high PLR ( P  = 0.029). In addition, univariate analysis with Cox proportional hazards modeling adjusted by IPW showed that PLR (≥150) (hazard ratio, 1.396; 95% CI, 1.051–1.855; P  = 0.021) was significantly associated with overall survival. Conversely, univariate analysis with Cox proportional hazards modeling adjusted only by IPW showed that PLR (≥150) (hazard ratio, 1.254; 95% CI, 1.016–1.549; P  = 0.035) was significantly associated with progression-free survival. PLR values were not independently associated with therapeutic responses before or after IPW-adjusted logistic regression analysis. Conclusions: PLR predicted overall survival in patients with unresectable HCC who received lenvatinib.